Pengaruh Media Pembelajaran Video Animasi Terhadap Minat dan Kemampuan Membaca Siswa Kelas III di UPTD SD Negeri Pendabah 1 Kamal - Purnama, Anggraeni Marina; Kusmiyati (eductum: Jurnal Literasi Pendidikan, 2024)
This study aims to examine the impact of animated video media on the reading interest and skills of third-grade students at UPTD SD Negeri Pendabah 1, Kecamatan Kamal. Recognizing the challenges faced by young learners in engaging with traditional reading exercises, this research focuses on how visual and interactive elements in animated videos can enhance students' motivation and comprehension in reading activities. The experimental method was employed with a pre-test and post-test design to assess the differences in students’ reading interest and proficiency before and after the intervention.The study involved a sample of third-grade students divided into experimental and control groups, where the experimental group was exposed to animated video media for reading sessions, while the control group followed conventional reading instruction. Analysis of the results indicated a significant increase in both reading interest and skills within the experimental group compared to the control group. Specifically, the animated videos captured students' attention, making reading sessions more engaging and thus contributing to a stronger motivation to read. The visual and interactive qualities of the videos appeared to aid in understanding and retaining reading materials, aligning with theories that suggest multimedia can enhance cognitive engagement in young learners.In conclusion, this study suggests that integrating animated video media as an educational tool can be highly effective in improving students' reading interest and ability. The findings imply that incorporating engaging multimedia elements in reading instruction can play a crucial role in motivating students and improving their learning outcomes. Schools and educators are encouraged to consider such media as a viable strategy to foster literacy skills in early education.